用于数字化制造标准弧齿锥齿轮机床调整参数的反求研究 - 徐文丽; 徐文芳; 徐文生; 龚红燕; 李玉书 (Jixie Chuandong, 2010)
Reverse algorithm for machine tool settings of standardized spiral bevel gear used in digitized manufacturing is derived.It is developed based on mathematical model and coordinate measurement of gear tooth surface.Real machine tool settings can be determined by these equations;Correctness of the reverse algorithm is proved through computer simulation,a modified Powell’s hybrid method is applied to solve these equations,a numerical example is given.